Konsep Moderasi Beragama pada QS. Al-Baqarah 143 dalam Kitab Tafsir Marah Labid dan Al Misbah - Islam, Fahmi; Rahmi, Aufa Dzakiyyah (Lathaif: Literasi Tafsir, Hadis dan Filologi, 2024)
At present, Muslims are still faced with two challenges, first, there is still a tendency to be extreme among Muslims in understanding the Qur'an, they impose their understanding in the midst of Muslim society, even to the point of using violence in spreading their understanding. Secondly, there is another tendency to relax the extremism in terms of religion so that it can lead to negative actions and thoughts that come from outside, namely other cultures and civilizations. Therefore, this research aims to find out the concept of religious moderation Qs. Al-Baqarah [2]: 143 in the Marah Labid and Al-Misbah commentaries, which have different paradigms and characteristics. This research uses the method of comparison (muqarran), which takes the point of view and interpretation process of two mufassirs, namely Nawawi Al-Bantani in the interpretation book Marah Labid and Quraish Shihab. The discussion of religious moderation in the two mufassirs is very necessary to do because it will help get an understanding of the moderate attitude in the life of society and the state that is easy to understand and understand. The concept of religious moderation in Qs. Al-Baqarah 143 according to Nawawi al-Bantani is fair, choice, knowledge and charity (work) always think before doing something and tolerance while according to Quraish Shihab moderate, exemplary, impartial middle position between the left and right camps, fair and balanced more to the nature of openness to differences. This interpretation can of course be influenced by their biases as mufassirs who are influenced by various factors of their lives and also have implications for the acceptance of an understanding of religious moderation that is easily understood by the community.